Sex-specific spatial use of the winter foraging areas by Magellanic penguins and assessment of potential conflicts with fisheries during winter dispersal - Dodino, Samanta Graciela (2021)
Magellanic penguins (Spheniscus magellanicus) disperse widely during winter and are a major consumer of marine resources over the Patagonian Shelf. Magellanic penguins were equipped with geolocators at Martillo Island in late February- early March 2017 and recaptured at the beginning of the next breeding season to recover the devices and to collect blood samples for stable carbon (δ13C) and nitrogen (δ15N) isotope analysis. We evaluated their whole winter dispersal and their trophic niche by sex during the last month of the winter dispersal. Also, we evaluated their spatial overlap with bottom trawl and shrimp fisheries using data from satellite fisheries monitoring. Penguins dispersed northwards up to 42°S and showed latitudinal spatial segregation between sexes during May to August (females were located further north than males). In contrast, during the last month of the winter dispersal females were located more southerly and showed lower trophic position than males. Also, females did not dive as deep as males during winter. We found high overlap between both fisheries and penguin?s spatial use in regions with documented interaction. However, no sex-specific statistical differences with fisheries overlap were found. Our results highlight the importance of understanding the spatial domains of each sex and assessment of their potential conflicts with bottom trawl fishery and shrimp fishery during the winter period.